Corrigendum to ‘Exposure to the Polychlorinated biphenyl mixture Aroclor 1254 elicits neurological and cardiac developmental effects in early life stage zebrafish (Danio rerio)’ [Chemosphere 371 (2025), 144023] - Corey S. Green; Jeffrey M. Morris; Jason T. Magnuson; Rachel Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Daniel Schlenk; Aaron P. Roberts (Chemosphere, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Aroclor 1254 impairs visual and neurosensory signaling pathways independent of the aryl hydrocarbon receptor in larval zebrafish - Jason T. Magnuson; Corey S. Green; Jeffrey M. Morris; Rachel R. Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Aaron P. Roberts; Daniel Schlenk (Aquatic Toxicology, 2026)

Influence of cardiotoxicity on visual function in developing zebrafish (Danio rerio) exposed to Deepwater Horizon crude oil - Rachel R. Leads; Jason T. Magnuson; Justin B. Greer; Corey S. Green; Daniel Schlenk; Aaron P. Roberts (Aquatic Toxicology, 2025)

The global imprint of shale weathering on molybdenum isotope ratios in river waters - Quentin Charbonnier; Edward T. Tipper; Robert G. Hilton; Corey Archer; Derek Vance (Earth and Planetary Science Letters, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Correction to: Insular and mainland interconnectivity in the movements of oceanic manta rays (Mobula birostris) off Mexico in the Eastern Tropical Pacific - Robert D. Rubin; Katherine R. Kumli; A. Peter Klimley; Joshua D. Stewart; James T. Ketchum; Edgar M. Hoyos‑Padilla; Felipe Galván‑Magaña; Aldo A. Zavala‑Jiménez; Iliana A. Fonseca‑Ponce; Megan Saunders; P. Santiago Dominguez‑Sanchez; Paul Ahuja; et al. (Environmental Biology of Fishes, 2025)

Insular and mainland interconnectivity in the movements of oceanic manta rays (Mobula birostris) off Mexico in the Eastern Tropical Pacific - Robert D. Rubin; Katherine R. Kumli; A. Peter Klimley; Joshua D. Stewart; James T. Ketchum; Edgar M. Hoyos-Padilla; Felipe Galván-Magaña; Aldo A. Zavala-Jiménez; Iliana A. Fonseca-Ponce; Megan Saunders; P. Santiago Dominguez-Sanchez; Paul Ahuja; et al. (Environmental Biology of Fishes, 2025)

Corrigendum to ‘Exposure to the polychlorinated biphenyl mixture Aroclor 1254 elicits neurological and cardiac developmental effects in early life stage zebrafish (Danio rerio)’ [Chemosphere 371(2025):144023] - Corey S. Green; Jeffrey M. Morris; Jason T. Magnuson; Rachel Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Daniel Schlenk; Aaron P. Roberts (Chemosphere, 2025)

Characterizing pyrethroid and fipronil concentrations in biosolids - John Wheeler; Gabrielle P. Black; Michelle L. Hladik; Corey J. Sanders; Jennifer Teerlink; Luann Wong; Xuyang Zhang; Robert Budd; Thomas M. Young (Science of The Total Environment, 2025)

Exposure to the Polychlorinated biphenyl mixture Aroclor 1254 elicits neurological and cardiac developmental effects in early life stage zebrafish (Danio rerio) - Corey S. Green; Jeffrey M. Morris; Jason T. Magnuson; Rachel R. Leads; Claire R. Lay; Michel Gielazyn; Lisa Rosman; Daniel Schlenk; Aaron P. Roberts (Chemosphere, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Uncovering the hidden world of riverbed sediments: The role of sediment heterogeneity and cross-bar channel fills in the hydrogeochemical dynamics of the hyporheic zone - Jeffery T. McGarr; Pei Li; Robert G. Ford; Teagan Kleman; Colton Fields; Julie Hobbs; Lydia Lupton; Emma Poston; Thomas Marsh; Leah Trutschel; Ken M. Fritz; Annette Rowe; et al. (Journal of Hydrology, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Learnings from rapid response efforts to remotely detect landslides triggered by the August 2021 Nippes earthquake and Tropical Storm Grace in Haiti - Pukar Amatya; Corey Scheip; Aline Déprez; Jean-Philippe Malet; Stephen L. Slaughter; Alexander L. Handwerger; Robert Emberson; Dalia Kirschbaum; Julien Jean-Baptiste; Mong-Han Huang; Marin K. Clark; Dimitrios Zekkos; et al. (Natural Hazards, 2023)
On August 14, 2021, a Mw 7.2 earthquake struck the Tiburon Peninsula of western Haiti triggering thousands of landslides. Three days after the earthquake on August 17, 2021, Tropical Storm Grace crossed shallow waters offshore of southern Haiti triggering more landslides worsening the situation. In the aftermath of these events, several organizations with disaster response capabilities or programs activated to provide information on the location of landslides to first responders on the ground. Utilizing remote sensing to support rapid response, one organization manually mapped initiation point of landslides and three automatically detected landslides. The 2021 Haiti event also provided a unique opportunity to test different automated landslide detection methods that utilized both SAR and optical data in a rapid response scenario where rapid situational awareness was critical. As the methods used are highly replicable, the main goal of this study is to summarize the landslide rapid response products released by the organizations, detection methods, quantify accuracy and provide guidelines on how some of the shortcomings encountered in this effort might be addressed in the future. To support this validation, a manually mapped polygon-based landslide inventory covering the entire affected area was created and is also released through this effort.

An integrated assessment of the 1,4-dioxane cancer mode of action and threshold response in rodents - Mark Lafranconi; Janet Anderson; Robert Budinsky; Lisa Corey; Norman Forsberg; Joanna Klapacz; Matthew J. LeBaron (Regulatory Toxicology and Pharmacology, 2023)

Mitigation of cadmium uptake in Theobroma cacao L: efficacy of soil application methods of hydrated lime and biochar - Gideon Ramtahal; Pathmanathan Umaharan; Carisa Davis; Corey Roberts; Anand Hanuman; Leon Ali (Plant and Soil, 2022)

Many cameras make light work: opportunistic photographs of rare species in iNaturalist complement structured surveys of reef fish to better understand species richness - Christopher J. Roberts; Adriana Vergés; Corey T. Callaghan; Alistair G. B. Poore (Biodiversity and Conservation, 2022)
Citizen science is on the rise, with growing numbers of initiatives, participants and increasing interest from the broader scientific community. iNaturalist is an example of a successful citizen science platform that enables users to opportunistically capture and share biodiversity observations. Understanding how data from such opportunistic citizen science platforms compare with and complement data from structured surveys will improve their use in future biodiversity research. We compared the opportunistic fish photographs from iNaturalist to those obtained from structured surveys at eight study reefs in Sydney, Australia over twelve years. iNaturalist recorded 1.2 to 5.5 times more fish species than structured surveys resulting in significantly greater annual species richness at half of the reefs, with the remainder showing no significant difference. iNaturalist likely recorded more species due to having simple methods, which allowed for broad participation with substantially more iNaturalist observation events (e.g., dives) than structured surveys over the same period. These results demonstrate the value of opportunistic citizen science platforms for documenting fish species richness, particularly where access and use of the marine environment is common and communities have the time and resources for expensive recreational activities (i.e., underwater photography). The datasets also recorded different species composition with iNaturalist recording many rare, less abundant, or cryptic species while the structured surveys captured many common and abundant species. These results suggest that integrating data from both opportunistic and structured data sources is likely to have the best outcome for future biodiversity monitoring and conservation activities.

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

Impact of an SGLT2-loss of function mutation on renal architecture, histology, and glucose homeostasis - Corey B. Hughes; George M. Mussman; Phil Ray; Robert C. Bunn; Virgilius Cornea; Kathryn M. Thrailkill; John L. Fowlkes; Iuliana Popescu (Cell and Tissue Research, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Citizen science data accurately predicts expert-derived species richness at a continental scale when sampling thresholds are met - Corey T. Callaghan; J. Dale Roberts; Alistair G. B. Poore; Ross A. Alford; Hal Cogger; Jodi J. L. Rowley (Biodiversity and Conservation, 2020)

Velocity Curvature Index: a Novel Diagnostic Biomarker for Large Vessel Occlusion - Samuel G. Thorpe; Corey M. Thibeault; Seth J. Wilk; Michael O’Brien; Nicolas Canac; Mina Ranjbaran; Christian Devlin; Thomas Devlin; Robert B. Hamilton (Translational Stroke Research, 2019)

Cotton (Gossypium hirsutum L.) mutants with reduced levels of palmitic acid (C16:0) in seed lipids - Corey N. Thompson; Bralie R. Hendon; Deepika Mishra; Jacob M. Rieff; Cindy C. Lowery; Kimberly C. Lambert; Travis W. Witt; Steven J. Oswalt; Efrem Bechere; C. Wayne Smith; Roy G. Cantrell; Brendan R. Kelly; et al. (Euphytica, 2019)

Feeding ecology of invasive lionfish (Pterois volitans and Pterois miles) in the temperate and tropical western Atlantic - Jonathan Peake; Alex K. Bogdanoff; Craig A. Layman; Bernard Castillo; Kynoch Reale-Munroe; Jennifer Chapman; Kristen Dahl; William F. Patterson III; Corey Eddy; Robert D. Ellis; Meaghan Faletti; Nicholas Higgs; et al. (Biological Invasions, 2018)

Networking our science to characterize the state, vulnerabilities, and management opportunities of soil organic matter - Jennifer W. Harden; Gustaf Hugelius; Anders Ahlström; Joseph C. Blankinship; Ben Bond‐Lamberty; Corey R. Lawrence; Julie Loisel; Avni Malhotra; Robert B. Jackson; Stephen Ogle; Claire Phillips; Rebecca Ryals; et al. (Global Change Biology, 2018)
Soil organic matter ( SOM ) supports the Earth's ability to sustain terrestrial ecosystems, provide food and fiber, and retains the largest pool of actively cycling carbon. Over 75% of the soil organic carbon ( SOC ) in the top meter of soil is directly affected by human land use. Large land areas have lost SOC as a result of land use practices, yet there are compensatory opportunities to enhance productivity and SOC storage in degraded lands through improved management practices. Large areas with and without intentional management are also being subjected to rapid changes in climate, making many SOC stocks vulnerable to losses by decomposition or disturbance. In order to quantify potential SOC losses or sequestration at field, regional, and global scales, measurements for detecting changes in SOC are needed. Such measurements and soil‐management best practices should be based on well established and emerging scientific understanding of processes of C stabilization and destabilization over various timescales, soil types, and spatial scales. As newly engaged members of the International Soil Carbon Network, we have identified gaps in data, modeling, and communication that underscore the need for an open, shared network to frame and guide the study of SOM and SOC and their management for sustained production and climate regulation.

Prostate cancer derived prostatic acid phosphatase promotes an osteoblastic response in the bone microenvironment - Sandy R. Larson; Jessica Chin; Xiaotun Zhang; Lisha G. Brown; Ilsa M. Coleman; Bryce Lakely; Martin Tenniswood; Eva Corey; Peter S. Nelson; Robert L. Vessella; Colm Morrissey (Clinical & Experimental Metastasis, 2014)

Continental‐Scale Governance and the Hastening of Loss of Australia's Biodiversity - Euan G. Ritchie; Corey J. A. Bradshaw; Chris R. Dickman; Richard Hobbs; Christopher N. Johnson; Emma L. Johnston; William F. Laurance; David Lindenmayer; Michael A. McCarthy; Dale G. Nimmo; Hugh H. Possingham; Robert L. Pressey; et al. (Conservation Biology, 2013)

Is a cancer diagnosis a teachable moment for the patient’s relative who smokes? - Robert A. Schnoll; E. Paul Wileyto; Frank T. Leone; Corey Langer; Richard Lackman; Tracey Evans (Cancer Causes & Control, 2013)

Pre‐reproductive survival in a tropical bird and its implications for avian life histories - Corey E. Tarwater; Robert E. Ricklefs; J. Dylan Maddox; Jeffrey D. Brawn (Ecology, 2011)
The factors that affect survival until reproduction are essential to understanding the organization of life histories within and among species. Theory predicts, for example, that survival until reproduction influences the optimum level of reproductive investment by parents, which might partly explain prolonged parental care in species with high first‐year survival. Tests and refinements of life‐history theory have been hampered, however, by a lack of field‐based estimates of pre‐reproductive survival, especially for tropical species, which have been the subject of many comparative analyses. Tropical species are predicted to have higher first‐year survival and delayed reproduction compared to Northern Hemisphere species. We estimated survival until reproduction, age at first reproduction, and sources of variation in juvenile survival in a Neotropical passerine, the Western Slaty‐Antshrike ( Thamnophilus atrinucha ), in central Panama. We observed that fledged antshrikes had 76% survival through the dependent period and 48% survival to the age of 1 year; survival rate was lowest during the first week after leaving the nest. Timing of fledging within the breeding season, fledgling mass, and age at dispersal influenced survival, while sex of offspring and year did not. Individuals did not breed until two years of age, and post‐fledging pre‐reproductive survival was 41% of annual adult survival. High survival until reproduction in antshrikes balanced their low annual productivity, resulting in a stable population. Survival during the post‐fledging period of dependence and the first year of independence in the Western Slaty‐Antshrike exceeded estimates for Northern Hemisphere species. This difference appears to be associated with the extended post‐fledging parental care, delayed dispersal, low costs of dispersal, and the less seasonal environment of antshrikes.

A bupropion smoking cessation clinical trial for cancer patients - Robert A. Schnoll; Elisa Martinez; Kristina L. Tatum; Dorothy M. Weber; Natalie Kuzla; Marcella Glass; John A. Ridge; Corey Langer; Curtis Miyamoto; E. Paul Wileyto; Frank Leone (Cancer Causes & Control, 2010)

Complex equilibria in the maintenance of boundaries: experiments with mussel beds - Carlos D. Robles; Robert A. Desharnais; Corey Garza; Megan J. Donahue; Carlos A. Martinez (Ecology, 2009)
Stationary boundaries of sedentary species may belie dynamic processes that form them. Our aim was to test an implication of an evolving body of theory, that such boundaries are manifestations of complex regulatory dynamics. On rocky shores of British Columbia, large‐scale field experiments altered the densities of predatory sea stars ( Pisaster ochraceus ), causing shifts in the location of the lower vertical boundaries of their prey, sea mussels ( Mytilus californianus ). While control mussel beds remained unchanged, experimental reductions of sea star densities caused the downward extension of the lower boundaries, and experimental increases in sea stars densities caused the upward recession of the lower boundary well into the zone presumed to be a spatial refuge from predation. Cleared plots prepared within the initial boundaries were recolonized to varying degrees, depending on predator densities. After 30 months, plots on sea star removal sites showed high densities of adult mussels, control plots showed intermediate densities, and sea star addition plots showed only a sparse cover of alternative prey. Observations by divers at high tide showed that as small prey were depleted progressively from removal, to control, to addition sites, correspondingly larger mussels were attacked, including very large individuals comprising the lower boundary of addition sites. The findings contradict classic theory of zonation based on static prey refuges and support an alternative theory in which boundaries are maintained by complex, spatially structured equilibria.

Issues related to implementing a smoking cessation clinical trial for cancer patients - Elisa Martinez; Kristina L. Tatum; Dorothy M. Weber; Natalie Kuzla; Anna Pendley; Kirsten Campbell; John A. Ridge; Corey Langer; Curtis Miyamoto; Robert A. Schnoll (Cancer Causes & Control, 2009)

Differential expression of angiogenesis associated genes in prostate cancer bone, liver and lymph node metastases - Colm Morrissey; Lawrence D. True; Martine P. Roudier; Ilsa M. Coleman; Sarah Hawley; Peter S. Nelson; Roger Coleman; Ya-Chun Wang; Eva Corey; Paul H. Lange; Celestia S. Higano; Robert L. Vessella (Clinical & Experimental Metastasis, 2008)

Feast or famine: evidence for mixed capital–income breeding strategies in Weddell seals - Kathryn E. Wheatley; Corey J. A. Bradshaw; Robert G. Harcourt; Mark A. Hindell (Oecologia, 2008)

Quantitative trait loci for hip dysplasia in a crossbreed canine pedigree - Rory J. Todhunter; Raluca Mateescu; George Lust; Nancy I. Burton-Wurster; Nathan L. Dykes; Stuart P. Bliss; Alma J. Williams; Margaret Vernier-Singer; Elizabeth Corey; Carlos Harjes; Richard L. Quaas; Zhiwu Zhang; et al. (Mammalian Genome, 2005)

Male-biased sex ratios in New Zealand fur seal pups relative to environmental variation - Corey J. A. Bradshaw; Robert G. Harcourt; Lloyd S. Davis (Behavioral Ecology and Sociobiology, 2003)

Calcium dependence of action potential-induced endocytosis in chromaffin cells - Shyue-An Chan; Robert Chow; Corey Smith (Pflügers Archiv - European Journal of Physiology, 2003)

The winter migration of Adelie penguins breeding in the Ross Sea sector of Antarctica - Lloyd Davis; Robert Harcourt; Corey Bradshaw (Polar Biology, 2001)

Construction and analysis of bacterial artificial chromosome libraries from a marine microbial assemblage - Oded Béjà; Marcelino T. Suzuki; Eugene V. Koonin; L. Aravind; Andrew Hadd; Linh P. Nguyen; Rachel Villacorta; Mojgan Amjadi; Corey Garrigues; Stevan B. Jovanovich; Robert A. Feldman; Edward F. DeLong (Environmental Microbiology, 2000)
Cultivation‐independent surveys of ribosomal RNA genes have revealed the existence of novel microbial lineages, many with no known cultivated representatives. Ribosomal RNA‐based analyses, however, often do not provide significant information beyond phylogenetic affiliation. Analysis of large genome fragments recovered directly from microbial communities represents one promising approach for characterizing uncultivated microbial species better. To assess further the utility of this approach, we constructed large‐insert bacterial artificial chromosome (BAC) libraries from the genomic DNA of planktonic marine microbial assemblages. The BAC libraries we prepared had average insert sizes of ≈ 80 kb, with maximal insert sizes > 150 kb. A rapid screening method assessing the phylogenetic diversity and representation in the library was developed and applied. In general, representation in the libraries agreed well with previous culture‐independent surveys based on polymerase chain reaction (PCR)‐amplified rRNA fragments. A significant fraction of the genome fragments in the BAC libraries originated from as yet uncultivated microbial species, thought to be abundant and widely distributed in the marine environment. One entire BAC insert, derived from an uncultivated, surface‐dwelling euryarchaeote, was sequenced completely. The planktonic euryarchaeal genome fragment contained some typical archaeal genes, as well as unique open reading frames (ORFs) suggesting novel function. In total, our results verify the utility of BAC libraries for providing access to the genomes of as yet uncultivated microbial species. Further analysis of these BAC libraries has the potential to provide significant insight into the genomic potential and ecological roles of many indigenous microbial species, cultivated or not.

The relationship between D 2 receptor occupancy and plasma levels on low dose oral haloperidol: a PET study - Shitij Kapur; Robert Zipursky; Paul Roy; Corey Jones; Gary Remington; Ken Reed; Sylvain Houle (Psychopharmacology, 1997)